Na2CeF6: A Highly Laser Damage‐Tolerant Double Perovskite Type Ce(IV) Fluoride Exhibiting Strong Second‐Harmonic Generation Effect - Tang, Ru‐Ling; Xu, Wei; Lian, Xin; Wei, Yue‐Qi; Lv, Yi‐Lei; Liu, Wenlong; Guo, Sheng‐Ping (Small (Weinheim an der Bergstrasse, Germany), 2024)
Perovskite structure compounds are significant candidates for designing new optical function materials due to their structural variability. Here, an inorganic tetravalent cerium fluoride, Na2CeF6, is derived from the perovskite structure through double‐site cation co‐substitution. Na2CeF6 crystalizes in the non‐centrosymmetric space group P6¯2m${P}^{\bar{6}}2m$. Edge‐sharing connected NaF9 and CeF9 polyhedra build the whole 3D structure of Na2CeF6. Importantly, it represents the first Ce(IV) fluoride nonlinear optical (NLO) crystal and can produce a strong and phase‐matchable second‐harmonic generation (SHG) effect of ≈2.1 times that of KH2PO4 (KDP), making it the strongest among non‐lone pair electron metal fluoride system. Further, it exhibits a high laser‐induced damage threshold (LIDT) of 74.65–76.25 MW cm−2, which is over 20 times that of AgGaS2. It also exhibits a wide transparent region (0.5−14.3 µm). This work provides a facile route for exploring high‐performance halide NLO materials. Here, an inorganic tetravalent cerium fluoride, Na2CeF6, is derived from the perovskite structure by double site cation substitution. It represents the first Ce(IV) fluoride nonlinear optical crystal and demonstrates a strong and phase‐matchable second‐harmonic generation effect (2.1 × KH2PO4). It also exhibits large laser‐induced damage threshold (over 20 × AgGaS2).